2014
DOI: 10.1177/0960327113520018
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study using pulmonary function tests and x-ray examination in toner-handling workers

Abstract: Objectives: This study uses pulmonary function tests and chest x-ray examinations to examine the relationship between toner-handling work and its health effects. Methods: The subjects were 1504 male workers in a Japanese toner and photocopier manufacturing company, in the age range from 19 to 50 years in 2003. Personal exposure measurements, pulmonary function tests, chest x-ray examinations, biomarker mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Compared with human volunteer or cross-sectional epidemiological studies, the evidence obtained by longitudinal epidemiological studies is quite limited, but longitudinal study results are needed to fully examine the health impact of particulate air pollutants associated with office machines, as far as chronic health effects are concerned. In a cohort study on toner and photocopier manufacturing workers conducted over 4 years, no evidence was obtained regarding the adverse effects on the pulmonary function or chest X-ray findings associated with toner-handling work, 25 26 although an increased prevalence of breathlessness was observed in association with toner-handling work. 27 However, those studies did not evaluate the incidence of abnormalities based on longitudinally observed data.…”
Section: Discussionmentioning
confidence: 98%
“…Compared with human volunteer or cross-sectional epidemiological studies, the evidence obtained by longitudinal epidemiological studies is quite limited, but longitudinal study results are needed to fully examine the health impact of particulate air pollutants associated with office machines, as far as chronic health effects are concerned. In a cohort study on toner and photocopier manufacturing workers conducted over 4 years, no evidence was obtained regarding the adverse effects on the pulmonary function or chest X-ray findings associated with toner-handling work, 25 26 although an increased prevalence of breathlessness was observed in association with toner-handling work. 27 However, those studies did not evaluate the incidence of abnormalities based on longitudinally observed data.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously reported on the detailed assessment of toner exposure [19][20][21][22]. In this study, every year between 2003 and 2010, several subjects randomly selected from among workers engaged in five work categories had their toner exposure measured using a personal dust sampler.…”
Section: Toner Exposure Assessmentsmentioning
confidence: 99%
“…Since a positive independent relationship between lung function impairment and abdominal obesity is well known [26], we adopted BMI as a confounding factor. As for other confounding factors we adopted, these were expected to affect the prevalence of respiratory symptoms based on published baseline studies [27,28] and interim reports [20][21][22]. In the analysis for the symptom wheezing without asthmatic response, only asthma was excluded as a confounding factor.…”
Section: Analysis Of Subjective Respiratory Symptomsmentioning
confidence: 99%
“…In model 3, we used the higher goodness-of-fit model in models 1 and 2 and adjusted the model using age at baseline, body mass index, smoking, asthma, allergic rhinitis, pneumonia, sinusitis, exposure to dust other than toner at work, and organic solventhandling work as confounding factors. Baseline surveys [21,27] and interim reports [22][23][24] have suggested that these variables may influence dependent variables. Additionally, in model 4, with regard to toner-handling work, analysis was performed using the three groups, that is, the highconcentration toner exposure group, low-concentration toner exposure group, and non-toner-handling group.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported our findings from detailed assessments of toner exposure levels [19,[21][22][23][24]. In particular, Matsuda et al described the details of the actual state of toner exposure in workers who handled toner in the same enterprise where this study was conducted.…”
Section: Toner Exposure Assessmentmentioning
confidence: 96%